Pengembangan Branding pada Produk-Produk Lokal di Desa Kerinjing, Kecamatan Tanjung Raja, Kabupaten Ogan Ilir, Sumatera Selatan - Hera Febria Mavilinda; Nyimas Dewi Murnila Saputri; Suhartini Karim; Lina Dameria Siregar; Yulia Hamdaini Putri; Fida Muthia; Cean Maria Bella (Lembaga Pengembangan Kinerja Dosen, 2025)
This Community Service Activity was conducted to develop branding on local products in Kerinjing Village, Tanjung Raja District, Ogan Ilir Regency, South Sumatra. This activity was carried out offline. The method of this community service activity was training and mentoring for participants. Participants in the activity were MSME actors engaged in food and beverage processing, convection, and several other fields. The community service activity began with a presentation of material, discussion, and direct practice of using media in making logos. In addition, participants were also directed to use social media to brand their products. The results of the community service activity showed that some participants understood the branding material and could use the Canva application to make their product logos, which will be used in packaging or distributed through social media. Successful branding will build a positive image for consumers, ultimately increasing consumer interest in the product.